Extra-Pulmonary Vein Triggers at de novo and the Repeat Atrial Fibrillation Catheter Ablation - Kim, Daehoon; Hwang, Taehyun; Kim, Min; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2021)
Background: Extra-pulmonary vein triggers can play a significant role in atrial fibrillation recurrence after catheter ablation. We explored the characteristics of the extra-pulmonary vein (PV) triggers in de novo and repeat atrial fibrillation (AF) catheter ablation (AFCA). Methods: We included 2,118 patients who underwent a de novo AFCA (women 27.6%, 59.2 ± 10.9 years old, paroxysmal AF 65.9%) and 227 of them conducted repeat procedures. All included patients underwent isoproterenol provocation tests at the end of the procedure, and then we analyzed extra-PV triggers-related factors. Results: Extra-PV triggers were documented in 11.7% of patients undergoing de novo AFCA (1.22 ± 0.46 foci per patient) and 28.6% undergoing repeat AFCA (1.49 ± 0.73 foci per patient). Older age and higher LA volume index in de novo procedures and women, diabetes, and higher parasympathetic nerve activity (heart rate variability) in repeat-AFCA were independently associated with the existence of extra-PV triggers. The septum (19.9%), coronary sinus (14.7%), and superior vena cava (11.2%) were common extra-PV foci. Among 46 patients who were newly found to have mappable extra-PV triggers upon repeat procedures, 15 (32.6%) matched with the previous focal or empirical extra-PV ablation sites. The rate of AF recurrence was significantly higher in patients with extra-PV triggers than in those without after de novo (HR 1.91, 95% CI 1.54–2.38, p < 0.001) and repeat procedures (HR 2.68, 95% CI 1.63–4.42, p < 0.001). Conclusions: Extra-PV triggers were commonly found in AF patients with significant remodeling and previous empirical extra-PV ablation. The existence of extra-PV triggers was independently associated with poorer rhythm outcomes after the de novo and repeat AFCA.